2017
DOI: 10.1115/1.4037500
|View full text |Cite
|
Sign up to set email alerts
|

Investigations of Compressible Turbulent Flow in a High-Head Francis Turbine

Abstract: Dynamic stability of the high-head Francis turbines is one of the challenging problems. Unsteady rotor–stator interaction (RSI) develops dynamic stresses and leads to crack in the blades. In a high-head turbine, vaneless space is small and the amplitudes of RSI frequencies are very high. Credible estimation of the amplitudes is vital for the runner design. The current study is aimed to investigate the amplitudes of RSI frequencies considering a compressible flow. The hydro-acoustic phenomenon is dominating the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 34 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…16(a) and 16(b). Equations 7and (8) were used to estimate the synchronous and asynchronous components of the pressure pulsations, respectively. The amplitude of the synchronous component was almost identical to the amplitude observed at locations S1 and S3.…”
Section: -14mentioning
confidence: 99%
See 1 more Smart Citation
“…16(a) and 16(b). Equations 7and (8) were used to estimate the synchronous and asynchronous components of the pressure pulsations, respectively. The amplitude of the synchronous component was almost identical to the amplitude observed at locations S1 and S3.…”
Section: -14mentioning
confidence: 99%
“…4 Furthermore, hydraulic turbines experience unstable flow conditions and high amplitude pressure pulsations during the transient cycles. [5][6][7][8][9][10] The pressure amplitudes are primarily dependent on the instantaneous rate of the guide vanes' movements and the runner's speed. 11,12 For the load acceptance cycle, the power output from the hydraulic turbine increases by opening the guide vanes.…”
Section: Introductionmentioning
confidence: 99%
“…The LES is expected to be able to answer the research questions associated with the challenging flow conditions present in the turbine blade cascade. Previous work 35,41 showed the benefit of compressible flow simulations over the incompressible flow in the Francis turbine. The flow compressibility accounts for the effect of pressure waves and reflection from the guide vanes and the draft tube similar to the actual turbine.…”
Section: Introductionmentioning
confidence: 99%
“…The highest amplitude corresponds to the runner blade passing frequency, and the second highest amplitude is the RVR frequency. These two frequencies were also observed in the calculation of Francis pump-turbines performed by Iliev et al [35]; whereas, only 15.0 times that of the runner rotational frequency was reported in some of the papers by Trivedi et al [36][37][38]. Based on the simulation results in this study, it can be concluded that the pressure wave of RVR is able to travel upstream (from the draft tube domain to the runner domain, and then to vaneless space), although the amplitude of fluctuation decreases, indicating that the oscillating intensity gradually recedes.…”
Section: In Vaneless Spacementioning
confidence: 67%